**Double Bracket Factorisation**

Starter

Expand the following expressions:

(x - 5)(x + 7)

(x - 3)(x + 3)

Factorising Quadratics

x - 4x -5

x - 81

**L.O. - To recognise when a quadratic factorises 2 brackets, and complete the factorisation.**

2

First to 15

2x(4x - 5) 3x(3x - 4) 3x(2y - 3x) 2r(4t + 3r) 6c(3c - 4b)

(x-9)(x+8) (x-6)(x+2) (x+7)(x+9) (x+16)(x-9) (x-7)(x-3)

(x-3)(x+3) (x-10)(x+10) (x-6)(x+6) (x-12)(x+12) (2x-7)(2x+7)

2

Starter

Expand the following expressions:

(x - 5)(x + 7) = x + 2x - 35

(x - 3)(x + 3) = x - 9

2

2

Factorising Quadratics

x - 4x -5

x - 81

2

2

(x - 5)(x + 1)

(x + 9)(x - 9)

Main Activity 1

Match the quadratics with their

factorised form.

Main Activity 1

Match the quadratics with their

factorised form.

Plenary

Plenary

**Key**

Examples

Examples

**Activities**

**Activity**

Answers

Answers

**Worked**

Example

Example

x - bx

ab

x

x

2

a

b

ax - ab

bx

x - bx + ax - ab

-b + a = 4

ab = 5

x - bx

2

ax - ab

x

b

a

bx

ab

x - bx + ax - ab

-b + a = 0

ab = 81

x

Factorising Quadratics

x + 7x + 12

x - 3x + 2

2

2

Factorising Quadratics

x + 7x + 12

x - 3x + 2

2

2

x

x

a

b

x

ax

bx

ab

x + ax + bx + ab

a + b = 7

ab = 12

2

2

x

x

a

b

ab

ax - ab

x - ax -

(bx - ab)

bx - ab

2

x - ax - bx + ab

- a - b = - 3

ab = 2

2

**Worked**

Example

Example